Analisis Pembelajaran Pendidikan Agama Islam pada Anak Berkebutuhan Khusus Di SLB Quridha Ilmi Kecamatan Tapalang Kabupaten Mamuju - Abdul Malik; Yuyun Sri Wahyuni; Prabu Rohman (Education and Learning Journal, 2023)
The foundation of this examination is that scientists see the troubles of learning Islamic Strict Schooling in kids with unique necessities, to be specific the comprehension of youngsters with extraordinary necessities which is restricted to something conceptual and requires substantial clarifications. Accordingly, Islamic Strict Schooling educators need to carry out discoveries that can give accommodation to understudies in SLB, specifically understudies with unique requirements to grasp the learning material well. This study analyzes the examination of Islamic strict schooling learning for youngsters with exceptional requirements at SLB Quridha Ilmi, Tapalang Locale, Mamuju Regime. This exploration is an engaging subjective examination. The subjects in the review were PAI educators and understudies of Kids with Extraordinary Necessities, while the item in the review was an examination of Islamic Strict Schooling learning for youngsters with unique requirements, while the sources in the review were associates, guardians, and instructors. Information was gathered through perception, meetings, and documentation. Information investigation utilized is. The consequences of the review presumed that the Examination of Islamic Strict Schooling Learning for understudies with extraordinary requirements at SLB Quridha Ilmi. Remain noticeable like educating and learning exercises overall. During the growing experience, there are understudies with exceptional necessities who are as yet joined by guides and the people who are not generally going with, and for understudies who are not generally going with in class, the educator will guide them with extremely restricted capacities in the ABK field. Supporting variables in the examination of Islamic Strict Training learning at SLB Quridha Ilmi, Tapalang Locale, Mamuju Regime: parental help, educators will direct calmly, the presence of ABK associates, the presence of schools upheld by the public authority, the job of understudies who regard one another. Restraining factors in Islamic Strict Schooling Learning; the shortfall of exceptional ABK educators, the shortfall of extraordinary ABK offices and framework, and the shortfall of unique ABK supporting books.